Field Evaluation of Rice Cultures for Resistance against Gall Midge, Orseolia oryzae - Kumar, R. Shravan; Reddy, A. Venkat; Chandra, B. Satish; Prasad, K. Rajendra; Hari, Y.; Nagabhushanam, U.; Ashwini, D.; Reddy, R. Uma (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during kharif, 2021 (June–November) at Regional Agricultural Research Station, Warangal, Telangana, India to evaluate rice cultures for resistance against gall midge (biotype 4M). Screening of 200 rice cultures developed in different research stations of PJTSAU, Hyderabad was done against gall midge along with susceptible check under natural field conditions at RARS, Warangal. Susceptible check TN-1 was grown for every 9 entries and also as border rows. Observations on gall midge incidence were recorded twice at 31–34 and 58–62 days after transplanting and then percentage of silver shoots was worked out. Observations were recorded by counting the total number of plants, damaged plants, total number of tillers and total number of silver shoots. At 58–62 DAT, 90–100% hill (plant) damage and 9.72 to 21.79% tiller damage was recorded in TN-1. Gall midge incidence among test entries was ranged from 0–100% hill (plant) damage and 0–16.67% silver shoots. Among the 200 test entries evaluated against gall midge, three entries viz., RDR-2751, IBT-GM-7 and IBT-GM-36 had shown highly resistant reaction (Nil damage), eight entries viz., JGL-36147, JMS24B, KNM 12392, KNM 11596, IBT WGL-2, IBT WGL-21, IBT WGL-31 and MLT-E-K21-66 had shown resistant reaction (<1% silver shoots). Seventy-four entries had shown moderately resistant reaction (1–5% silver shoots) against local gall midge population. All the moderately resistant entries recorded >10% hill (plant) damage.